Evaluating the Effect of Cinnarizine on Promastigotes and Amastigotes forms of Leishmania major - Sarouey, Lima A.; Rahimi-Moghaddam, Parvaneh; Tabatabaie, Fatemeh; Khanaliha, Khadijeh (Infectious Disorders - Drug Targets, 2020)
As an important global disease, cutaneous leishmaniasis is associated with complications such as secondary infections and atrophic scars. The first line treatment with antimonials is expensive and reported to have serious side effects and enhance resistance development. The main objective of this study was to evaluate the effect of Cinnarizine on standard strains of Leishmania major because of paucity of information on this subject. Methods: In this experimental study, four concentrations of the drug (5, 10, 15 and 20 μg/ml) were added to Leishmania major cultures at 24, 48 and 72 hours intervals. MTT assays were performed to determine parasite viability and drug toxicity. Leishmania major promastigotes were augmented to the in vitro cultured macrophages (J774 cells) and then incubated for 72 hours. Half maximal inhibitory concentration (IC50) was ascertained by counting parasites. The inhibitory effect of the drug was compared with that of Glucantime. Flow-cytometry was performed to investigate apoptosis. Each test was repeated thrice. Results: The IC50 values of Cinnarizine after 72 hours were calculated to be 34.76 μg/ml and 23.73 μg/ml for promastigotes and amastigotes, respectively. The results of MTT assays showed 48 % promastigote viability after 72 hour-exposure to Cinnarizine at 20 μg/ml concentration. Programmed cell death in promastigote- and amastigote-infected macrophages was quantified to be 13.66 % and 98.7 %, respectively. Flow- cytometry analysis indicated that Cinnarizine induced early and late apoptosis in parasites. All treatments produced results which differed significantly from control group (P<0.05). Conclusion: Cinnarizine showed low toxicity with anti-leishmanial and apoptosis effects on both promastigote and intracellular amastigote forms. Therefore, we may suggest further assessment on animal models of this drug as candidates for cutaneous leishmaniasis therapy.
Keywords: Cinnarizine